Lexicography in the borderland between knowledge and non-knowledge : general lexicographical theory with particular focus on learner's lexicography - Tarp, Sven (Lexicographica: Series Maior, v. 134., 2008)
The book contains a state-of-the-art summary of the theoretical discussions within the field of lexicography during the last decades. On this basis it presents and argues for a new general theory, called the function theory. It goes on to develop this theory in one single field, i.e. learners lexicography where it both formulates the basic elements of a general theory for learners dictionaries as well as a number of specific theories for special subfields such as selection, meaning, semantic relations, morphology, syntactic properties and word combinations. It contains a big number of examples extracted from existing dictionaries which are discussed from the point of view of the theories formulated.